Wombat goes walkabout - Morpurgo, Michael; Birmingham, Christian (Cambridge, Mass. : Candlewick Press, 2000)
While looking for his mother, Wombat meets many animals that are not impressed with his talent for digging and thinking, but when a fire approaches, they change their minds.
Booklist
Kirkus Review
Pub Weekly
2.8
K-3
K-3
Keywords: Animals -- Fiction; Lost children -- Fiction; Wombats -- Fiction; Animals -- Fiction; Missing children -- Fiction; Wombats -- Fiction; Australia -- Fiction; Australia -- Fiction